Factors associated with the acceptance of telemedicine services in Dusit model prototype area - Nontawat Benjakul; Utoomporn Wongsin; Sukhontha Siri; Chardsumon Prutipinyo (Scientific Reports)
Abstract The Dusit Model, a prototype area in Bangkok, Thailand, integrates telemedicine into primary and tertiary care to reduce overcrowding and promote equitable access. This study aimed to identify factors influencing telemedicine acceptance using an extended Technology Acceptance Model (TAM). A cross-sectional study was conducted among 389 participants using Vajira@Home. Variables included demographics, the extended Technology Acceptance Model (TAM), and telemedicine acceptance. Descriptive statistics, chi-square tests, and multivariate binary logistic regression were employed. Telemedicine acceptance was significantly correlated with generation, perceived ease of use (adjusted OR = 3.95, p = 0.047), and facilitating conditions (adjusted OR = 5.78, p = 0.013). Compared to Generation Z, Baby Boomers and Generation X had lower odds of acceptance (OR = 0.01 and 0.22, respectively). Model fit was confirmed (AUC = 0.79; Hosmer-Lemeshow p > 0.05). Generation, usability perceptions, and infrastructure support critically influence telemedicine acceptance. Policy should prioritize digital literacy for older adults, improve user experience, and invest in infrastructure to enhance equitable adoption.